Application of Prim Algorithm to an Electricity Network in Cimahi - Lusiani, Anie; Sartika, Euis; Nuryati, Neneng; Suhartini, Ida (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2025)
Prim's algorithm is an algorithm that is applied to determine the minimum spanning tree to optimize a network. In this research, the Prim algorithm will be applied to minimize the length of electrical cables used in an electricity distribution network. The data needed to build an initial model is the number of electricity poles on an electricity network, the position of the electricity poles, and the length of the cable connecting the two electricity poles. The electricity network used is in the management area of PT. PLN UP3 Cimahi, West Java. This initial model is represented by a weighted connected graph, where an electricity substation or an electricity pole is a vertex and an electricity cable connecting two electricity poles is an edge in the graph. The weight of this graph is the length of the cable. After the Prim algorithm is run on this graph, the minimum spanning tree is obtained which is the shortest length of electrical cable needed to connect all electricity poles, namely 1258.05 meters. When compared to the length of the existing cable that is being used, which is 1275.86 meters, the results of this study provide a cable efficiency of 17.81 meters. Thus, it is expected to provide cost efficiency arising from the price of the cable and its installation costs. This result is expected to provide input to PT. PLN UP3 Cimahi as an energy efficiency effort launched by the government.